A dual mode step-down switched-capacitor DC-DC converter with adaptive switch width modulation. (August 2018) - Liu, Lianxi; Chen, Hao; Hua, Tianyuan; Mu, Junchao; Zhu, Zhangming; Yang, Yintang
Abstract: This paper proposes a step-down switched-capacitor (SC) DC-DC converter with pulse frequency modulation (PFM) and burst mode. This design proposes a novel dual mode control strategy to achieve high performance over a wide load range. PFM is adopted at heavy load to achieve the small output voltage ripple while burst mode is adopted at light load to improve transient response and power efficiency. To further improve the efficiency, an adaptive switch width modulation (ASWM) is proposed to reduce switching losses. The measured results show that the proposed four conversion ratios converter can operate with a 2.0–3.6 V input voltage range, load current from 0 to 2 mA at the output voltage of 1.2 V. The peak power efficiency is up to 84.2% from a 2.7 V input voltage supply at a load current of 2 mA. At a load of 60 μA, the burst mode achieves an 11% maximum efficiency improvement, and the average efficiency improvement of 6% is achieved with ASWM.